2020
DOI: 10.1026/2191-9186/a000464
|View full text |Cite
|
Sign up to set email alerts
|

Das Vorleseverhalten von Eltern mit Kindern in den ersten drei Lebensjahren in Zusammenhang mit familiärer Lernumwelt und Sprachentwicklung

Abstract: Zusammenfassung. Während die Bedeutung frühen Vorlesens für die weitere Entwicklung von Kindern bereits in vielen Forschungsarbeiten nachgewiesen wurde, fehlen aktuelle Daten zum Vorleseverhalten von Eltern mit Kindern unter 3 Jahren. Ziel der Studie war daher eine repräsentative Erhebung und deskriptive Beschreibung der Vorleselandschaft in Deutschland, von Familien mit Kindern im Alter von 3 bis 39 Monaten. In face-to-face Interviews mit Eltern ( N = 523) wurden Einstellungen zum Vorlesen, Vorlesebeginn und … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The positive correlations between digital and analog HLEs in the toddler age group show that parents who actively involve their children in educational "analog" activities in this early phase of development do so with digital media, too. This finding aligns with previous research that showed that parents of children below the age of 3 years who read more often to their children also tended to show a greater frequency in various other activities, such as singing, playing with dolls, and doing crafts (Wirth et al, 2020b). We found that children's digital HLE activities rapidly increase with age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive correlations between digital and analog HLEs in the toddler age group show that parents who actively involve their children in educational "analog" activities in this early phase of development do so with digital media, too. This finding aligns with previous research that showed that parents of children below the age of 3 years who read more often to their children also tended to show a greater frequency in various other activities, such as singing, playing with dolls, and doing crafts (Wirth et al, 2020b). We found that children's digital HLE activities rapidly increase with age.…”
Section: Discussionsupporting
confidence: 91%
“…Digital media are commonplace nowadays in families, and European children grow up in media-rich homes (Chaudron et al, 2015). As children's immediate caregivers usually interact with digital media daily, children consider digital devices as very important (Wirth et al, 2020b). Toddlers and preschoolers learn by observing their parents and by interacting with older siblings, and from an early age onward, they are in contact with a wide range of digital tools daily and imitate older family members' usage (Wong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here, aspects such as the onset, frequency, and quality of shared reading which can be summarized as cultural praxis and the number of books at home as an indicator for cultural capital are specific predictors of children's linguistic and literacy outcomes (McElvany et al, 2009;Niklas, 2015). All these aspects are part of a global HLE construct (e.g., Cohrssen et al, 2016;Wirth et al, 2020). However, not much is known about the association of parental attitudes toward shared reading with the HLE, whether these attitudes should be integrated into a broader construct of the HLE or whether they should be treated as an independent variable, and about the association among attitudes, HLE, and children's linguistic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The home learning environment is an important predictor for children's early and later competencies development (Melhuish et al, 2008;Niklas and Schneider, 2017a). Here, shared reading is an important aspect of the HLE and should start early in children's life and should be part of a regular routine in the family (Niklas et al, 2016a;Wirth et al, 2020). However, little work has focused on the role that parental literacy attitudes play in this context (Bingham, 2007;Skibbe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the HLE acts as a mediator between more distal family characteristics and child outcomes. Further, research indicates that the HLE may not only predict concurrent children's early literacy and numeracy competencies (e.g., Burghardt et al, 2020, Napoli and, but also later achievement in school (e.g., as well as more general cognitive abilities (e.g., Howard et al, 2017; and socio-emotional outcomes (e.g., Wirth et al, 2020). Despite the research on the HLE and the findings in recent years, we still do not know how best to operationalize the HLE, through which specific mechanisms the HLE impacts children's learning, and which facets of the HLE are the most important.…”
Section: Children's Competencies Development In the Home Learning Environmentmentioning
confidence: 99%